Methodological model for economic and accounting valuation of environmental goods and services –EGS- in the municipality of Miraflores Boyacá - Camargo-López, Claudia Marcela; Ochoa-Sanabria, Nayarith; Martínez-Rodríguez, Olga Cecilia; Amézquita-Medina, Claudia Esperanza (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
This paper addresses the theoretical and conceptual bases related to economic valuation of environmental goods and services for designing of a methodological model, as well as approaches for categorization, identification and classification of such goods in the municipality of Miraflores. We apply the valuation "Cascade El Ombligo" in such a way to allow making decisions on a project of creation of a natural park in this water reserve.